Fuentes para la historia de la union general de trabajadores - Fundación Pablo Iglesias; Nájera, Aurelio Martin; Quintana, Antonio González (Madrid: FPI, 1988)
"Aurelio Martin Najera, Antonio Gonzales Quintana"